If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12 + -4y = 2(y + 9) Reorder the terms: 12 + -4y = 2(9 + y) 12 + -4y = (9 * 2 + y * 2) 12 + -4y = (18 + 2y) Solving 12 + -4y = 18 + 2y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-2y' to each side of the equation. 12 + -4y + -2y = 18 + 2y + -2y Combine like terms: -4y + -2y = -6y 12 + -6y = 18 + 2y + -2y Combine like terms: 2y + -2y = 0 12 + -6y = 18 + 0 12 + -6y = 18 Add '-12' to each side of the equation. 12 + -12 + -6y = 18 + -12 Combine like terms: 12 + -12 = 0 0 + -6y = 18 + -12 -6y = 18 + -12 Combine like terms: 18 + -12 = 6 -6y = 6 Divide each side by '-6'. y = -1 Simplifying y = -1
| 2.50x=500+0.35x | | 16a+28= | | 150x+50y=8395 | | (2a/a^2)^-2 | | 50(x+5)=a | | 200x+100y=12995 | | 3k(3k+10)=0 | | (2a/a^2)^2 | | 5x-2x=x+30 | | 3x-2=5x-19 | | 1-x=-9 | | 12a+8b= | | 7/8(16) | | 8x-4=-10x-3 | | 6(x-9)=24 | | 12x+5y=24547 | | 36w^2+39w+75=-2w-4 | | 1-6r=4-3r | | n+6=-12 | | 4(3x-2)=22 | | 39+4y-1=14y-11-3y | | 6y+8=3y+8 | | Lots(1000)=3 | | 10y-9=4y+3 | | 7x+19-2x-7= | | 8y^2x= | | 25-6x=5-8x | | -7/8*16 | | X/5-6=-10 | | 13=6x-3-5x | | -7/8x16 | | E^x^1/6 |